Strengthening early childhood education using smartphones in India - Nirupam Bajpai; Radhika Iyengar; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Early Childhood Education encompasses an interlinked gamut of elements critical for a child's cognitive social and emotional development. The first six years of development in a child's life are critical to their overall development and well-being. According to UNICEF, 'Investing in Early Childhood Development is one of the most cost-efficient and powerful strategies to achieve fair and sustainable development. India's development trajectory is critically linked to investments in healthcare and education. Achieving the Sustainable Development Goals (SDGs) is firmly anchored on investing in human capital and inclusive growth. Anganwadi Centers, part of the Integrated Child Development Services program, provides essential early childhood services offered by the ICDS across the lengths and breadth of the country. They cater to India's challenge of providing nutrition and healthcare options to children and mothers through counseling, pre-school education, immunization, and the supply of medical, health, and nutritional resources. The environment, inputs, and support that children receive in their first eight years will have an enormous impact on the rest of their lives - not only in terms of their performance in school but on a wide range of other outcomes that extend far beyond school. In recent years India has made significant progress in strengthening the policy framework for early childhood. The Government of India released the National Early Childhood Care and Education (ECCE) Policy in 2013, and subsequently a National Curriculum Framework and Quality Standards. Together, these documents provide a comprehensive framework for promoting access, equity, and quality in ECCE. State governments have designed their curricula in the light of this national framework. For the preprimary education sector, smartphones are envisioned to help in delivering a meaningful early childhood education, with autonomy to reflect the local context and the setting. ICT-driven innovative approaches have been contributing to the service delivery of the Anganwadi centers. This would call for investments in high-quality interventions for young children and are therefore cost-effective ways of improving outcomes both for individual children, especially in the case of vulnerable or disadvantaged children, and for the society as a whole. This paper also includes an operational model that could be implemented for "quick-wins" by leveraging technology to achieve short term and medium terms gains. The paper lays out activities that could be carried in a typical rural Aaganwadi settings and using ICT to enhance its current functioning. Finally, the paper concludes by suggesting pathways forward on the potential of using ICT for enhancing the quality of ECE.
Keywords: 330; Frühkindliche Bildung; Bildungspolitik; Informationstechnik; Mobiltelefon; Indien